Baker, Herbert (Sir) 1904. Archdeacon Furse House Parktown Johannesburg. Plans sections and elevations. - Baker, Herbert (Sir) (My University, 2011)
Baker, Herbert (Sir) 1904. Archdeacon Furse House Parktown Johannesburg. Plans sections and elevations. watercolour paint and pencil on paper.
Baker, Herbert (Sir) 1904. Archdeacon Furse House Parktown Johannesburg. Plans sections and elevations. Watercolour paint and pencil on paper 560x775
Keywords: Baker, Herbert (Sir) 1904. Archdeacon Furse House Parktown Johannesburg. Plans sections and elevations. watercolour paint and pencil on paper.